2018
DOI: 10.5899/2018/metr-00096
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Anxiety and Prevention Strategy: An Attempt to Support Students and Strengthen Mathematics Education

Abstract: In the process of reaching a medium income country, science, mathematics and technology have become an emphasis of Ethiopia. But, currently, students' interest to study mathematics and ability in mathematics is declining. This study therefore aimed to investigate the prevalence of mathematics anxiety and its effect on students' current mathematics achievement. Additionally, by grounding on the literature, some strategies supposed to reduce the negative effects of math anxiety were identified for practice. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
(10 reference statements)
0
8
0
2
Order By: Relevance
“…Looking at our daily activities, mathematics applies to cooks, farmers, carpenters, mechanics, shopkeepers, doctors, and musicians, to mention a few. Therefore, we can say that everybody needs mathematics (Shishigu, 2018).…”
mentioning
confidence: 99%
“…Looking at our daily activities, mathematics applies to cooks, farmers, carpenters, mechanics, shopkeepers, doctors, and musicians, to mention a few. Therefore, we can say that everybody needs mathematics (Shishigu, 2018).…”
mentioning
confidence: 99%
“…As the characteristics of the respondents would show, somehow, the admitted senior high school students were less confident in terms of equipping themselves with mathematical skills. In the path model analysis of Shishigu (2018), prior mathematics achievement was the strongest predictor for mathematical anxiety and present achievement in mathematics.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of the study's findings point to a negative correlation between test anxiety and academic accomplishment. According to these data, an increase in test anxiety affects pupils' academic achievement (Oluoch, 2018;Dodeen H. M., 2014;Shishigu, 2018;and Syokwaa, 2014). However, in their research, Kavakci et al (2014) found no link between test anxiety and student academic achievement.…”
Section: Assessment Anxietymentioning
confidence: 97%